Analysis Life Values From Habibie And Ainun Novels - Audry Putri Callista; Marudut Bernadtua Simanjuntak (Badan Penerbit STIEPARI Press, 2022)
This book tells the story of the life of a Habibie who has a big dream, namely to build an airplane as a dedication to Indonesia, and the life story of Ainun, a young, intelligent doctor. They are reunited and fall in love with each other until the end of their lives. They went through various life journeys together, to get a lot of life values that can be learned from the story. This book is based on the true story of Indonesia's third president. The stories they tell inspire many people from various aspects of life. This book was written by the President of Indonesia, namely Bacharuddin Jusuf Habibie. The purpose of this study is to find out the meaning of the values contained in the book. This study uses the narrative method to find out the values of life.